Does performance level affect initial ball flight kinematics in finger and wrist-spin cricket bowlers?. Issue 6 (19th March 2018) - Spratford, Wayne; Whiteside, David; Elliott, Bruce; Portus, Marc; Brown, Nicholas; Alderson, Jacqueline
ABSTRACT: Spin bowling plays a fundamental role within the game of cricket yet little is known about the initial ball kinematics in elite and pathway spin bowlers or their relationship to performance. Therefore, the purpose of this study was to record three-dimensional ball kinematics in a large and truly high level cohort of elite and pathway finger-spin (FS) and wrist-spin (WS) bowlers, identifying potential performance measures that can be subsequently used in future research. A 22-camera Vicon motion analysis system captured retro-reflective markers placed on the seam (static) and ball (dynamic) to quantify ball kinematics in 36 FS (12 elite and 24 pathway) and 20 WS (eight elite and 12 pathway) bowlers. Results indicated that FS bowlers delivered the ball with an increased axis of rotation elevation, while wrist-spin bowlers placed greater amounts of revolutions on the ball. It also highlighted that ball release (BR) velocity, revolutions and velocity/revolution index scores for both groups and seam stability for FS bowlers, and seam azimuth angle and spin axis elevation angle for WS bowlers, were discriminators of playing level. As such these variables could be used as indicators of performance (i.e. performance measures) in future research.